PENGARUH MARKETING SYARIAH DAN SERVICE EXCELLENT TERHADAP KEPERCAYAAN NASABAH MENGGUNAKAN TABUNGAN WADI’AH YAD DHAMANAH DI BMT MUAMALAT KALIBARU KABUPATEN BANYUWANGI - Sofi Faiqotul Hikmah; Ajeng Maulida (Jurnal Ekonomi Syariah Darussalam, 2020)
This study aims 1) To know and analyze the influence of sharia marketing variables on customer trust in savings, 2) To determine and analyze the effect of service excellent variables on customer trust, 3) To determine and analyze the effect of sharia marketing and service excellence variables on trust. The results of this study indicate that the variable partially sharia marketing on customer trust obtained a significant value with the t test with the value of Thitung> T tabel (2.658> 2.048) is the result of the t test shows that there is a positive influence between the sharia marketing variable (X1) on customer trust (Y ), partially the service excellent variable t test with a Thitung of (5.949> 2.048) the t test results show a positive influence between the service excellent variable (X2) on customer trust (Y), and the F test result is Fhitung = 68.815 with probability level 0.000b. So that (0.000b) is much smaller than 0.05 which means it is significant and based on the F test it is known that all the variables studied have a significant effect on variable Y.